The impact of stakeholder pressure on sustainability reporting - Ardheta, Preztika Ayu; Mustika, Maya; Mais, Rimi Gusliana; Safitri, Adelia (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
This study examines the impact of stakeholder pressure on sustainability reporting disclosure, focusing on three types of pressure: consumer pressure, employee pressure, and environmental pressure. The research objects are companies participating in ASSRAT from 2019 to 2022 and listed on the Indonesia Stock Exchange. This quantitative study employs a purposive sampling technique, resulting in a sample of 28 companies. The data used are secondary data obtained from the company’s official websites or the Indonesia Stock Exchange in the form of sustainability reports. Data analysis was conducted using multiple linear regression with the assistance of the EViews 10 software. The results indicate that consumer and employee pressure does not significantly affect sustainability reporting disclosure, while environmental pressure has a positive effect. Stakeholders tend to pressure companies to ensure their needs and objectives are addressed. Companies should remain transparent, particularly in economic, environmental, and social aspects. By disclosing comprehensive information in the sustainability report, companies demonstrate their commitment to transparency and maintaining strong relationships with stakeholders.